Running economy with shoes that elicit an involuntary forefoot strike in the habitual rear and non-rear foot strike runners - Yokoyama, S.; Arita, K.; Oshima, S.; Otsuka, J.; Okamoto, Y.; Kato, H.; Tazawa, S.; Hirai, S.; Kajiwara, Y.; Kunimasa, Y.; Amano, T. (Footwear Science, 2024)
The metabolic benefits of non-rearfoot strike (non-RFS) running remain unknown because no interventions can alter the runner`s foot strike patterns involuntarily. This study investigated whether wearing running shoes that elicit involuntary non-RFS running alters the oxygen consumption (VO2) of habitual RFS and non-RFS runners. Twenty-three male runners (10 RFS and 13 non-RFS) performed six bouts of 5-min treadmill runs at slow or fast speeds below lactate thresholds. The first three bouts were performed using either the control shoes (traditional racing shoes), the shoes that elicit involuntary non-RFS (Wave Duel Pro [WDP]), or the additional shoe used for a different purpose. Subsequently, participants ran another three bouts wearing each shoe in mirror order. Only the control and WDP shoes were analysed in this study. All participants were non-RFS runners when wearing WDP. The VO2 did not differ between WDP and control in habitual non-RFS runners (43.7 ± 5.6 and 43.5 ± 5.6 mL kg-1 min-1, respectively, P = 0.306 for the main effect of shoes). A small attenuation of VO2 by approximately 0.9% was observed with WDP compared with control in habitual RFS runners (43.9 ± 5.4 and 44.3 ± 5.6 mL kg-1 min-1, respectively, P = 0.025 for the main effect of shoes). The blood lactate concentration did not differ between WDP and control in both groups (P = 0.603). Similarly, the heart rate did not differ between the shoes in both groups (P = 0.166). The involuntary induction of non-RFS running by changing shoes has a negligible effect on reducing the running economy of habitual RFS runners.